Debt, debt sustainability and economic growth in Ghana - Cassiel Ato Baah Forson (West African Journal of Monetary and Economic Integration, 2019)
The purpose of the study is to test for debt sustainability as well as assess the impact of public debt on economic growth in Ghana using annual time series data spanning from 1970 to 2014. The study employed the fiscal reaction function suggested by Bohn (1998) to test for the sustainability of Ghana's debt. The neoclassical growth model was used to determine the relationship between debt and economic growth after controlling for other determinants of growth such as labour, capital, trade openness, government expenditure, inflation, and democracy. Findings from the Fully Modified OLS (FMOLS) estimates reveal that Ghana's debt is unsustainable although the evidence is weak. Results from the Autoregressive Distributed Lag (ARDL) estimates reveal that debt exerts a negative impact on economic growth in Ghana in both the long and short-run, however, the long-run impact of debt on economic growth is greater. The study recommends that government must make some efforts to direct borrowed funds into productive economic activities to enable the Ghanaian economy to grow itself out of debt
Keywords: H30; H60; H63; O40; 330; Debt; Economic Growth; Debt Sustainability; Fiscal Reaction Function